La description du déplacement en français, anglais et chinois mandarin: différentes stratégies de repérage - Boulin, Myriam (Neophilologica, 2014)
The mental representation of a perceived motion event varies according to the spatial location of the observer. Does that imply that a speaker systematically identifies himself as the locator of the event he is describing? In this article, I examined the use of deictic motion verbs (come, go) in each of these languages. The research was based on a survey conducted among French, English and Chinese speakers and on the analysis of two bilingual corpora. The results show that in Chinese the deictic center is generally the speaker, whereas it is the interlocutor in English, and neither the former nor the latter in French.